2009 IEEE International Ultrasonics Symposium 2009
DOI: 10.1109/ultsym.2009.5441852
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of nonlinear behaviour of power ultrasonic drilling horns

Abstract: In ultrasonic drilling, cutting and welding applications, ultrasonic devices are needed to generate large vibration velocities. It is renowned that whilst these devices are driven at high power their dynamic behaviour tends to exhibit nonlinear features. Until a fundamental understanding of this behaviour will not be achieved, and effective ways to control it developed, high power ultrasonics will unlikely find utilize in large scale industrial processes. This study is focused on the characterisation of the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This indicates that piezoceramic stack location does not influence this behavior as significantly as it does for the other nonlinear behaviors, resonant frequency shift and the jump phenomenon. However, studies of power ultrasonic devices have reported that the width of the hysteretic region can be significantly influenced by elevated piezoceramic element temperature and joint preloading in ultrasonic devices [19]. The temperature variation on the surface of the piezoceramic stack in this study was mea-sured to be 3.01°c, 2.98°c, and 2.07°c, during the bi-directional frequency sweeps between 1 and 50 V rms , for TI, TII, and TIII respectively.…”
Section: Nonlinear Regime Of Vibration: Duffing-type Systemmentioning
confidence: 58%
See 2 more Smart Citations
“…This indicates that piezoceramic stack location does not influence this behavior as significantly as it does for the other nonlinear behaviors, resonant frequency shift and the jump phenomenon. However, studies of power ultrasonic devices have reported that the width of the hysteretic region can be significantly influenced by elevated piezoceramic element temperature and joint preloading in ultrasonic devices [19]. The temperature variation on the surface of the piezoceramic stack in this study was mea-sured to be 3.01°c, 2.98°c, and 2.07°c, during the bi-directional frequency sweeps between 1 and 50 V rms , for TI, TII, and TIII respectively.…”
Section: Nonlinear Regime Of Vibration: Duffing-type Systemmentioning
confidence: 58%
“…duffing-like behavior has been documented in piezoceramic elements and langevin transducers in previous studies [14]- [18]. although in the general solution the cubic term is responsible for duffing-like behavior, in power ultrasonic devices it is known to stem from several sources [19]. such behavior observed in the responses of piezoceramic elements (kept at constant temperature) has been attributed to the elastic compliance changing proportionally with the square of vibrational stress when excited above a vibrational threshold [12].…”
Section: Nonlinear Regime Of Vibration: Duffing-type Systemmentioning
confidence: 95%
See 1 more Smart Citation
“…The ultrasonic transducer is an actuator component that converts AC electric power into mechanical vibration to accelerate the removal of the hard and brittle materials [7], [8]. Generally, the output amplitude of ultrasonic transducer varies drastically with the driving frequency, and the maximum vibration amplitude can be achieved when it operates at the mechanical resonant frequency [9]. Therefore, the resonant frequency of the RUH should match with that of the transducer.…”
Section: Many Untraditional Machining Methods Including Abrasivementioning
confidence: 99%
“…Harkness et al from the University of Glasgow in the United Kingdom found through experiments that the introduction of torsional vibration on the basis of the longitudinal vibration of the sampling drilling tool can significantly improve the drilling efficiency of the ultrasonic drill (Bo, 2019). To realize the introduction of torsional vibration into the drilling tool, Harkness et al proposed the concept of a transducer, which uses the helical groove on the horn in the transducer to convert the longitudinal vibration into torsional vibration (Harkness et al, 2009, 2012; Mathieson et al, 2009). To achieve low drilling pressure drilling, the Jet Propulsion Laboratory of the United States proposed an Ultrasonic/Sonic Driller/Corer (USDC) with a drilling pressure of less than 5 N. Its structure is shown in Figure 8f, which consists of a piezoelectric transducer, a free mass block, and a drilling tool (Bar‐Cohen et al, 2005; Chang et al, 2004).…”
Section: Research Status Of Planetary Penetratorsmentioning
confidence: 99%